Creencias ambientales de estudiantes de Sociología de la Universidad Nacional del Centro del Perú - Álvarez Tolentino, Daniel (2020)
As part of their social responsibility, universities have been implementing environmental education strategies in response to the environmental crisis. Therefore, the Faculty of Sociology of the National University of               the Center of Peru (UNCP, spanish acronym) implemented an environmental curriculum complemented by courses in ethics and philosophy. This study aims to measure the environmental beliefs of undergraduate students in order to evaluate the impact of the strategy employed. To this end, the New Ecological Paradigm scale (NEP) was applied to 214 students enrolled in all semesters during the 2017-2018 academic period. The results showed a greater predominance of ecocentric beliefs (=3.9± 0.72), which demonstrated that the approach being implemented by the faculty is strengthening the environmental awareness of its students.   DOI: https://doi.org/10.31876/sl.v4i1.51